An Unbiased CO Survey toward the Northern Region of the Small Magellanic Cloud with the Atacama Compact Array. I. Overview: CO Cloud Distributions - Tokuda, Kazuki; Kondo, Hiroshi; Ohno, Takahiro; Konishi, Ayu; Sano, Hidetoshi; Tsuge, Kisetsu; Zahorecz, Sarolta; Goto, Nao; Neelamkodan, Naslim; Wong, Tony; Sewilo, Marta; Fukushima, Hajime; et al. (Astrophysical Journal, 2021)
We have analyzed the data from a large-scale CO survey toward the northern region of the Small Magellanic Cloud (SMC) obtained with the Atacama Compact Array (ACA) stand-alone mode of ALMA. The primary aim of this study is to comprehensively understand the behavior of CO as an H-2 tracer in a low-metallicity environment (Z similar to 0.2 Z (circle dot)). The total number of mosaic fields is similar to 8000, which results in a field coverage of 0.26 deg(2) (similar to 2.9 x10(5) pc(2)), corresponding to similar to 10% of the area of the galaxy. The sensitive similar to 2 pc resolution observations reveal the detailed structure of the molecular clouds previously detected in the single-dish NANTEN survey. We have detected a number of compact CO clouds within lower H-2 column density (similar to 10(20) cm(-2)) regions whose angular scale is similar to the ACA beam size. Most of the clouds in this survey also show peak brightness temperature as low as <1 K, which for optically thick CO emission implies an emission size much smaller than the beam size, leading to beam dilution. The comparison between an available estimation of the total molecular material traced by thermal dust emission and the present CO survey demonstrates that more than similar to 90% of H-2 gas cannot be traced by the low-J CO emission. Our processed data cubes and 2D images are publicly available.
CRIS-Team WoS Importer:2021-12-10